2017
DOI: 10.1016/j.heliyon.2017.e00446
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin gene expression and intracellular calcium changes in the giant freshwater prawn, Macrobrachium rosenbergii , in response to white spot symptom disease infection

Abstract: BackgroundDystrophin, an essential protein functional in the maintenance of muscle structural integrity is known to be responsible for muscle deterioration during white spot syndrome virus (WSSV) infection among prawn species. Previous studies have shown the upregulation of dystrophin protein in Macrobrachium rosenbergii (the giant freshwater prawn) upon white spot syndrome virus (WSSV) infection. The literature has also suggested the important role of calcium ion alterations in causing such muscle diseases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For example, sarcoplasmic calcium-binding protein which acts as a buffer to cytosolic Ca 2+ and maintains the intracellular Ca 2+ levels was found to have low expression levels in WSSV-infected P. monodon (Leu et al, 2007). Similarly, downregulation of dystrophin gene expression was attributed to metabolic changes, leading to an increase in Ca 2+ levels and loss of muscular integrity in the WSSV infected muscle tissues in M. rosenbergii (Noor et al, 2017).…”
Section: Average Of Dna Content In G2 Phasementioning
confidence: 99%
See 2 more Smart Citations
“…For example, sarcoplasmic calcium-binding protein which acts as a buffer to cytosolic Ca 2+ and maintains the intracellular Ca 2+ levels was found to have low expression levels in WSSV-infected P. monodon (Leu et al, 2007). Similarly, downregulation of dystrophin gene expression was attributed to metabolic changes, leading to an increase in Ca 2+ levels and loss of muscular integrity in the WSSV infected muscle tissues in M. rosenbergii (Noor et al, 2017).…”
Section: Average Of Dna Content In G2 Phasementioning
confidence: 99%
“…Similar results have been reported in the muscle tissue of the WSSV‐infected M . rosenbergii , which showed a significant increase in the amount of intracellular calcium from 3 hours post WSSV infection, with an overall increase of 1.6‐fold in the infected samples compared with the control samples (Noor et al, 2017). The other factors such as chronic Cu 2+ exposure of P .…”
Section: Sample Time Point (Hpi) Dna Content In G1 Phase Average Of Dna Content In G1 Phase Dna Content In G2 Phase Average Of Dna Contenmentioning
confidence: 99%
See 1 more Smart Citation
“…Some viruses can utilize the host Ca 2+ -associated pathway to promote their replication 31 . Previous research has shown that intracellular calcium increases after WSSV infection and CaMKK is activated by the increased cytoplasmic Ca 2+ 32 . It is unknown whether CaMKK activates AMPK signaling in shrimp.…”
Section: Introductionmentioning
confidence: 97%
“…We have shown previously that silencing genes of the ecdysone synthesis and signalling pathway impaired the development and survival of whitefly nymphs (Luan et al , ). Here we targeted dystrophin (Dys), a conserved protein essential for the development of the muscle system in humans and in many other organisms (Noor et al , ).…”
Section: Introductionmentioning
confidence: 99%